Required thoracic drainage through the respiratory tract during transbronchial biopsy using EBUS‐GS. Issue 4 (13th September 2015) - Yaguchi, Daizo; Ichikawa, Motoshi; Inoue, Noriko; Matsuura, Akinobu; Shizu, Masato; Imai, Naoyuki
Abstract: A 71‐year‐old woman was referred to our department due to an abnormal chest shadow. Imaging revealed a pulmonary nodule shadow in the left S6 segment, multiple small nodule shadows in the left pleura, and left pleural effusion. Transbronchial biopsy using endobronchial ultrasonography (EBUS) with a guide sheath was conducted. EBUS showed the probe of the sheath located in the lesion and biopsy was performed in this area. A yellow turbid fluid appeared in the sheath and vacuum aspiration resulted in collection of 200 mL of this fluid. We suspected that drainage occurred because the sheath tip had ruptured the pleural cavity. The pathological diagnosis was adenocarcinoma. It is likely that the EBUS images reflected pleural effusion adjacent to the lesion, and that the complication occurred because the biopsy was performed without awareness of these findings. This complication may be prevented by closer examination of echo findings and rotation of the X‐ray source to ensure performance of the biopsy directly under the pleura. Abstract : Transbronchial biopsy using endobronchial ultrasonography with a guide sheath (EBUS‐GS) is now becoming a common procedure for the diagnosis of peripheral pulmonary lesions, and the efficacy and safety of the procedure have been established. We report a rare case that required thoracic drainage through the respiratory tract for a complication that arose during transbronchial biopsy using EBUS‐GS.